2001
DOI: 10.1046/j.1365-2133.2001.144s58027.x
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy with vitamin D analogues

Abstract: Monotherapy with vitamin D analogues has been shown to be effective in the treatment of psoriasis. Vitamin D analogues have also been used in combination with other topical therapies, systemic therapies and phototherapy. In many instances, the efficacy of these other treatments can be maximized and adverse effects minimized when combined with vitamin D analogues. The combination of a topical corticosteroid with a vitamin D analogue can work synergistically to improve efficacy and reduce the side-effects from b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Findings for some poor responding patient categories make a strong case for trying such alternatives instead of digressing guidelines resorting to over treatment or under treatment with traditional drugs. Vitamin D3 analogues are reported to be as effective as steroids and yield a synergistic benefit in psoriasis, reducing required mutual doses39. Tazarotene, the newer retinoid is especially inhibitory to the dermal infiltration of inflammatory cells40.…”
Section: Discussionmentioning
confidence: 99%
“…Findings for some poor responding patient categories make a strong case for trying such alternatives instead of digressing guidelines resorting to over treatment or under treatment with traditional drugs. Vitamin D3 analogues are reported to be as effective as steroids and yield a synergistic benefit in psoriasis, reducing required mutual doses39. Tazarotene, the newer retinoid is especially inhibitory to the dermal infiltration of inflammatory cells40.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of calcipotriol in the treatment of psoriasis has primarily been attributed to its effects on epidermal proliferation and differentiation/keratinisation [10-12] although the effects on skin infiltrating T cells are relevant to its mode of action [13,14]. Calcipotriol has been shown to reduce CD3, CD4, CD8 and CD45RO positive T-cells in psoriatic skin [15].…”
Section: Discussionmentioning
confidence: 99%
“…[108,109] There was a reduction of CD3 + CD4 + CD8 + memory T cells in psoriatic skin [110] as well as significant reduction in biomarkers of epidermal proliferation, differentiation, and lymphocyte infiltration. [110][111][112] Likewise, in a study with K252a, a high affinity NGF-R blocker, we have shown that within 2 weeks of administration in SCID mouse psoriatic xenograft model, it reduced clinical, immunological as well as pathological characteristics of psoriasis.…”
Section: Drugs Targeting Proliferation and Differentiationmentioning
confidence: 96%